The effect of a semiconductor filler on the properties of low-density polyethylene - Aliguliyeva Kh.V.; Aleskerova D.M. (Reviews of Modern Science, 2023)
In the presented work, by thermal pressing of low-density polyethylene and Bi0.5Sb1.5Te3, in a powdered state with nano-crystallite sizes of 80 nm, composite materials with different contents of semiconductor filler were obtained. The obtained composites were subjected to X-ray phase analysis, X-ray images were obtained on a Bruker D 2 PHASER X-ray diffractometer, the microrelief of the surface of composites with semiconductor fillers was studied by atomic force microscopy methods depending on the volume content of the semiconductor material Bi0.5Sb1.5Te3. Raman scattering spectra of LDPE+ Bi0.5Sb1.5Te3 composites with an excitation wavelength of 532nm were studied on a three-dimensional confocal Romanov micro-spectrometer NANOFINDER. The radius of the cross section of the laser beam incident on the composite was equal to 4mkm. The radiation receiver was a cooled SSD camera (-700C) operating in the photon counting mode. It is shown that the thermal expansion of the crystal causes a linear shift of the Romanov peak caused by a change in temperature. Similarly, the mechanism that changes the frequency of phonons causing mixing of the raman peak is an anharmonic interaction that changes the phonon frequency in the opposite direction to thermal expansion. It is revealed that peak shifts in the studied composites are associated with changes in mechanical stresses at the matrix–filler interface. Frequency shifts of raman scattering peaks and a change in the peak responsible for vibrations across the crystal layers, with an increase in the filler concentration, may indicate an increase in the matrix pressure on the filler microsurfaces and an increase in the anharmonicity of vibrations.